Alpha and low gamma embedded with white noise binaural beats modulating working memory among Malaysian young adults: an exploratory fMRI study - Aloysius, Nursabrina Mohd Firdaus (2021)
Introduction: Exposure to alpha and gamma binaural beats (BB) have provided inconsistent findings in its modulating role of working memory (WM). White noise (WN) has acted as a control condition. Objective: The study aims to explore the effect of load on the effectiveness of WN embedded BB on WM performance using functional magnetic resonance imaging. Method: The research utilised experimental, block-design n-back task paradigm. Results: Six young adults (3 males and 3 females) within the Kota Bharu vicinity were recruited with mean age of 23.5 ± 0.84. The twoway repeated measures ANOVA (p<0.05) on response accuracy shows there is no significant main effect for conditions and load. The interaction effect of conditions and load on response accuracy (2=.171) demonstrates slight improvement in response accuracy The two-way repeated measures ANOVA (p<0.05) of reaction time (RT) shows a significant difference in the main effect of load, in particular during 1-back condition post BB. There is no interaction effect of conditions and load on RT. For GWN and AWN exposure, one sample t-test (p<0.05,uncorrected) suggests that the activation of posterior cingulate gyrus are associated with attentional modulation and supplementary motor area is closely related to WM mechanism respectively. Two-way repeated measures ANOVA (p<0.05,uncorrected) of the WM task further supports the aforementioned modulation in post-BB activations with the activation of thalamic regions in GWN and frontoparietal regions in AWN. Conclusion: The preliminary findings suggest that WN embedded BB should be considered further as a non-invasive WM improvement method amongst clinical and non-clinical population.